Book Review of "The International Atomic Energy Agency: Historical Reflections, Current Challenges and Future Prospects" - Ágota Duró (International Journal of Nuclear Security, 2023)
Edited by Joseph F. Pilat and published by Routledge, The International Atomic Energy Agency: Historical Reflections, Current Challenges and Future Prospects is an insightful and illuminating book. This collection is an updated and expanded version of 16 papers, as well as the keynote address, presented at the 2017 Conference on the International Atomic Energy Agency (IAEA) held at the Woodrow Wilson International Center for Scholars in Washington, DC.